Development of Cost Effective Assay for Phosphate Contents in Seafood and Frozen Food Samples - Atittaya Charumram (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The cost effective assay of phosphate contents in sea food and frozen food samples was developed with aims to make use of commercially available test strip for on-site analysis. Colors on the strip relate to phosphate in test solution. The color intensity can be evaluated via a mobile phone. A calibration graph was found to be linear in a range of 25-100 mg/L, with an equation of y = 0.5552x + 8.8333, R² = 0.9721. Investigation on sample preparation at site was made. Finally, a test solution was then measured for phosphate by the test strip and via the calibration graph. Samples taken in markets in Chiang Mai were assayed for phosphate. It was found that the contents were 927 to 7446 mg/kg.